The Role of Physical Education in Developing Positive Character Traits in Elementary School Students - Nurafiati, Suastika; Asri, Ariana; Suparman; Hasbillah, Muhammad; Arham, Sarifuddin (JOURNAL RESPECS (Research Physical Education and Sports), 2025)
This study investigates the role of physical education in fostering positive character development among elementary school students, focusing on collaboration, discipline, responsibility, and respect. The research addresses a gap in understanding the broader impact of physical education beyond physical fitness, emphasizing its potential to shape students' social and moral values. The study was conducted at SD Negeri Mamajang 3 Makassar using a qualitative design, involving interviews with teachers and students, classroom observations, and data analysis. A total of 30 students participated in the study, representing diverse demographic backgrounds. The findings reveal that physical education significantly contributes to character development. Approximately 60% of students demonstrated a high level of collaboration, while 67% showed strong discipline in adhering to instructions and maintaining punctuality. Responsibility was evident in 40% of students who actively assumed leadership roles, and respect was the most dominant character, with 73% of students displaying respectful behavior toward peers. These results highlight the effectiveness of structured physical education programs in promoting positive character traits through teamwork-based and leadership-oriented activities. The study concludes that physical education is a critical tool for holistic student development, providing both physical and character-building benefits. However, the research is limited to a single school and primarily relies on qualitative methods, which may restrict the generalizability of the findings. Future research should explore longitudinal studies and include larger, more diverse samples to strengthen the validity and applicability of the results. Policymakers and educators are encouraged to integrate character-building strategies into physical education curricula to enhance student development comprehensively.